A Sinergi Nalar Religius dan Nalar Modern - Putra, Andi Eka; Muslimin; Bagaskara, Arya (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the relevance of Muhammad Abed Al-Jabiri's epistemology to the dynamics of santri education in modern Islamic boarding schools that integrate religious and general education. Al-Jabiri developed an epistemology with three forms of reasoning: bayani, irfani, and burhani, each of which reflects a different approach to acquiring knowledge. Bayani reasoning emphasizes revealed texts as the main source of knowledge, while irfani reasoning emphasizes intuition and spiritual experience, and burhani reasoning focuses on rationality and empiricism. This article also discusses how Al-Jabiri's thinking plays a role in reconstructing santri education to be more adaptive to the challenges of modernity, by balancing religious values ​​and scientific rationality. In the application of Al-Jabiri's epistemology, especially burhani reasoning, knowledge is obtained through systematic deduction, induction, and empirical observation. However, in the context of the development of modern science, this model is considered limited, so M. Amin Abdullah proposed the addition of the concept of abduction, a more dynamic and flexible hypothetical inference method. Abduction allows knowledge to develop through further testing of hypotheses, which opens up space for creative reasoning in dealing with complex phenomena.